Antenatally diagnosed congenital anomalies-trend in tertiary care hospital - Kishore, Kamal; Dey, Madhusudan; Gaba, Ashisha; K. P., Shijith; Bhatt, Reema Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Antenatally diagnosed, congenital abnormalities of the fetus are frequently offered antenatal surgical consultation in all tertiary care hospitals to adequately counsel prospective parents. We aimed to assess the current trends in antenatally diagnosed congenital malformations of fetus in patients who had presented to our hospital for reassessment or surgical consultation and these patients were counselled and prognosticated after confirmation of anomaly at our centre accordingly. Methods: This was a retrospective study of all the cases diagnosed antenatally with fetal abnormalities. All cases were referred to either pediatric surgery outpatient department or fetal medicine subunit of a tertiary care centre from January 2017-December 2018. The complete records of these pregnant women were perused, presence and type of anomaly confirmed at our centre and trends about types of anomalies analysed. Results: A total of 209 women were analyzed for antenatal anomalies, out of these patients medical termination of pregnancy was offered to 27 (12.9%) patients, in which 38 anomalies were detected and in 182 (87%) patients pregnancy was continued to delivery. A total of 223 anomalies were detected in this group with some patients having fetuses with more than one anomaly. Gastrointestinal abnormalities were present in 94 (51.6%) patients of those who delivered and accounted for the most common anomaly followed by CNS abnormality which accounted for 39 (21.4%) of total abnormalities and genitourinary abnormalities contributed to 28 (13.3%) of abnormalities. A total of 85.2% of patients were referred after 20 weeks. Conclusions: The significant number of patients with major congenital anomalies are still diagnosed at a date later than permissible time for termination of gestation (20 weeks). There were cases where anomaly scan was done at a later gestation and then there were others where inadequate counselling made patient to present late for prognostication. However, there are certain anomalies that are picked up late and are likely to be missed in the routine anomaly scan. Therefore, antenatal detection and early referral helps in offering early counselling and better outcome for pregnancy.